2009
DOI: 10.1021/jp9060329
|View full text |Cite
|
Sign up to set email alerts
|

Resonance Energy Transfer Between Luminescent Quantum Dots and Diverse Fluorescent Protein Acceptors

Abstract: We characterized the resonance energy transfer interactions for conjugates consisting of QD donors self-assembled with three distinct fluorescent protein acceptors: two monomeric fluorescent proteins, the dsRed derivative mCherry or yellow fluorescent protein and the multi-chromophore bphycoerythrin light harvesting complex. Using steady-state and time-resolved fluorescence, we showed that nonradiative transfer of excitation energy in these conjugates can be described within the Förster dipole-dipole formalism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
95
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 111 publications
(100 citation statements)
references
References 48 publications
(141 reference statements)
5
95
0
Order By: Relevance
“…One can argue that it may not be possible to observe a rise in the emission intensity of the acceptor when the rise time is short and comparable to the finite time resolution of the experimental setup. However, the present case does not belong to this category as the QDs are [18,19,50] An acceptor need not be a fluorescence system, but when it is, the energy transfer efficiency (E) can be estimated from the enhancement in the acceptor fluorescence using Equation (1): [22] E ¼ ðI…”
Section: Fretmentioning
confidence: 99%
“…One can argue that it may not be possible to observe a rise in the emission intensity of the acceptor when the rise time is short and comparable to the finite time resolution of the experimental setup. However, the present case does not belong to this category as the QDs are [18,19,50] An acceptor need not be a fluorescence system, but when it is, the energy transfer efficiency (E) can be estimated from the enhancement in the acceptor fluorescence using Equation (1): [22] E ¼ ðI…”
Section: Fretmentioning
confidence: 99%
“…For the FRET decay of EYFP in our bioconjugates, we assigned the largest time of 22.6 ns to photons coming from directly excited QDs and leaked to the probed emission wavelengths; the 5.2 ns decay time represents the fluorescence decay of the FRET-excited EYFP and the 1.5 ns lifetime is the predicted rise time of the FRET process that should correspond to the most readily available FRET donor states. [51] We tested the nature of the interaction between the QDs and the fluorescent protein by performing similar experiments with the negatively charged QD 480 -MPA and EYFP under the same conditions as those used in the previous experiments. In contrast to that observed with positively charged QD 480 -PAH + , the steady-state emission intensity and the fluorescence lifetimes of QD 480 -MPA remained unchanged in the presence of EYFP ( Figure S2 in the Supporting Information).…”
Section: Effect On Qds Fluorescence Lifetime Of Ligands Bound By Elecmentioning
confidence: 99%
“…This study also reported the occurrence of FRET beyond 100 Å. Medintz et al [29,30] have demonstrated FRET using CdSe-ZnS (core-shell) QD donors self assembled with three distinct fluorescent protein acceptors. Water soluble CdSe-ZnS QDs covalently attached to human immunoglobulin G (IgG) have been shown to act as efficient FRET donors for fluorescent isothiocyanate (labelled with goat antihuman IgG) [31][32][33]. The CdSe-ZnS QDs have also been used for the development of self-assembled donor for long range FRET in a 3-chromophore FRET system.…”
Section: Introductionmentioning
confidence: 99%